An own-age bias in mixed- and pure-list presentations: No evidence for the social-cognitive account - Cronin, Sophie L.; Craig, Belinda; Lipp, Ottmar (WILEY, 2019)
© 2019 The British Psychological Society The own-age bias (OAB) is suggested to be caused by perceptual-expertise and/or social-cognitive mechanisms. Bryce and Dodson (2013, Psychology and Aging, 28, 87, Exp 2) provided support for the social-cognitive account, demonstrating an OAB for participants who encountered a mixed-list of own- and other-age faces, but not for participants who encountered a pure-list of only own- or other-age faces. They proposed that own-age/other-age categorization, and the resulting OAB, only emerge when age is made salient in the mixed-list condition. Our study aimed to replicate this finding using methods typically used to investigate the OAB to examine their robustness and contribution to our understanding of how the OAB forms. Across three experiments that removed theoretically unimportant components of the original paradigm, varied face sex, and included background scenes, the OAB emerged under both mixed-list and pure-list conditions. These results are more consistent with a perceptual-expertise than social-cognitive account of the OAB, but may suggest that manipulating age salience using mixed-list and pure-list presentations is not sufficient to alter categorization processes.